Spectrum handoff based on adaptive weights adjustment - Zhao, Zhi-jin; Zhang, Lu-ping; Wang, Hai-quan (IET communications, 2015)
Spectrum handoff is one of key technologies of cognitive radio. A spectrum handoff strategy based on adaptive weights adjustment is proposed, considering the effect of secondary users’ (SUs) transmission power, fading factor, bandwidth and channel availability on the target channel selecting. According to the principle of multi-attribute simple additive weight algorithm (MA-SAW), the expected effect function of each channel is obtained by analysis. Making full use of the change of the various factors in cognitive wireless network, the LMS adaptive algorithm of dynamic weights is put forward. Finally, the dynamic weights are applied to MA-SAW, to determine target channel to switch. The simulation results show that the proposed algorithm can reduce the switching times of SUs, and improve the effective transmission rate.